Neonatal Surgery And The Law: Rights, Responsibilities, And Regulations - Mishra, Hari Om; Kumar Singh, Arvind (Journal of Neonatal Surgery, 2025)
Neonatal surgery, a field dedicated to addressing congenital anomalies and acquired conditions in newborns, occupies a unique and sensitive position within the broader medical landscape. The patients, neonates, are inherently vulnerable, lacking the capacity for self-determination and reliant entirely on others for their well-being. The interventions, often life-saving, carry significant risks and frequently necessitate complex, life-altering decisions. This intersection of vulnerability and high stakes decision-making creates a complex web of ethical and legal considerations that demand careful navigation. This paper delves into the intricate interplay between neonatal surgery and the law, aiming to illuminate the key legal principles that underpin this specialized area of practice. It explores the legal frameworks that govern decision-making, emphasizing the crucial balance between respecting parental autonomy and safeguarding the best interests of the neonate.